The transcriptional repressor HEY2 regulates mitochondrial oxidative respiration to maintain cardiac homeostasis - Peilu She; Bangjun Gao; Dongliang Li; Chen Wu; Xuejiao Zhu; Yuan He; Fei Mo; Yao Qi; Daqing Jin; Yewei Chen; Xin Zhao; Jinzhong Lin; et al. (Nature Communications)
Abstract Energy deprivation and metabolic rewiring of cardiomyocytes are widely recognized hallmarks of heart failure. Here, we report that HEY2 (a Hairy/Enhancer-of-split-related transcriptional repressor) is upregulated in hearts of patients with dilated cardiomyopathy. Induced Hey2 expression in zebrafish hearts or mammalian cardiomyocytes impairs mitochondrial respiration, accompanied by elevated ROS, resulting in cardiomyocyte apoptosis and heart failure. Conversely, Hey2 depletion in adult mouse hearts and zebrafish enhances the expression of mitochondrial oxidation genes and cardiac function. Multifaceted genome-wide analyses reveal that HEY2 enriches at the promoters of genes known to regulate metabolism (including Ppargc1, Esrra and Cpt1) and colocalizes with HDAC1 to effectuate histone deacetylation and transcriptional repression. Consequently, restoration of PPARGC1A/ESRRA in Hey2- overexpressing zebrafish hearts or human cardiomyocyte-like cells rescues deficits in mitochondrial bioenergetics. Knockdown of Hey2 in adult mouse hearts protects against doxorubicin-induced cardiac dysfunction. These studies reveal an evolutionarily conserved HEY2/HDAC1-Ppargc1/Cpt transcriptional module that controls energy metabolism to preserve cardiac function.